PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR PPKn SISWA KELAS VI B SD NEGERI 002 KIYAP JAYA KECAMATAN BANDAR SEI KIJANG KABUPATEN PELALAWAN - Alfani ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This research was motivated by the low student learning outcomes PPKn SD Negeri 002 Kirap Jaya sixth grade students, this is evidenced by an average of only 62.14 student learning outcomes. While KKM is set at 65. To the researchers conducted a study with the aim to improve learning outcomes PPKn through the implementation of cooperative learning model type STAD. This research is a classroom action through the stages of planning, implementing action, observation and reflection. This research was conducted in two cycles. The subjects were students of class VI SD Negeri 002 Kirap Jaya with a number of students sebanya 40 students. The results of the research data showed that the learning outcomes of students has increased, this is evidenced by: (a) the activities of teachers has increased in the first cycle of the first meeting activity for teachers to get a score of 11 (45.83%), in the first cycle II meeting increased with a score of 14 ( 58.33%), the second cycle of the first meeting increased with a score of 19 (79.19%). And the second cycle II meeting increased with a score of 22 (91.66%). Activities of students has increased, at the first meeting the first cycle of activity students obtain a score of 10 (41.66%), at a meeting of the second cycle II with a score of 13 (54.16%), at a meeting I cycle II with a score of 17 (70, 83%). And at the second meeting of the cycle II with a score of 20 (83.33%); and (b) PPKn learning outcomes of students has increased At the base score / baseline number of students who completed is 20 students (50.00%) with a low category, the first cycle is the number of students who pass the 30 students (75.00%) with high category and the second cycle the number of students who pass the increase with the amount due totaling 36 students (90.00%) with a very high category.